Conservation Outside Forests in Indonesia : An Option to Untangle Authority Dualism in the Essential Ecosystem Area - Merdekawati, Agustina; Triatmodjo, Marsudi; Nurvianto, Sandy; Hasibuan, Irkham Afnan Trisandi; Purnamawati, Vivin; Agung, I Gusti Putu (Yustisia, 2022)
As a country rich in biodiversity, Indonesia has realised the importance of conducting conservation efforts beyond the designated conservation areas, where most of the biodiversity elements are located. In fact, the country has adopted the concept of Essential Ecosystem Areas (EEAs) into various statutory instruments. However, the implementation of EEA policies has faced various obstacles stemming from the dualism of authority between the central and regional governments in establishing and managing EEA. Act No. 23 of 2014 on Regional Government delegates the implementation to the provincial governments. At the same time, Government Regulation No. 28 of 2011 mandates that the exercise of EEA protection be integrated with conservation efforts conducted by the central government. Therefore, this study aims to analyse the legal implications of the dualism of authority in EEA implementation and provide recommendations for a regulatory scheme. The problem may be mitigated by considering the factors relevant to the regulatory implementation aspects. The results revealed that the existence of dualism of authority has had implications in several aspects, including the authority in establishing, managing and financing EEAs, which have prevented authorities from achieving the objectives of establishing EEAs. Thus, this study also recommends the integrated and modified implementation of EEA policies in several ways